2016
DOI: 10.7314/apjcp.2016.17.1.357
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Characteristics of Adult Acute Myeloid Leukemia - Tertiary Care Experience

Abstract: Background: Acute myeloid leukemia (AML) is an acquired clonal frequent malignant disorder of myeloid progenitor cells. Our aim was to study demographical and clinicopathological features of adult Pakistani AML patients at presentation. Materials and Methods: In this single centre study extending from January 2010 to December 2014, data were retrieved from the patient records with a predetermined performa and analyzed with SPSS version 22. Results: Overall 125 patients were diagnosed at our institution with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
4
7
0
Order By: Relevance
“…This nding in our study in accordance with other studies that reported M2 to be the most common subtype in their studies [1,4,20,21] and in contrast to other studies that showed a predominance of M1 in her study [16]. It is reported that different AML subtypes have different prognostic values [22]. FAB subtypes M0, M5, M6, and M7 are associated with the worst prognosis, while M2 and M4 a good prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…This nding in our study in accordance with other studies that reported M2 to be the most common subtype in their studies [1,4,20,21] and in contrast to other studies that showed a predominance of M1 in her study [16]. It is reported that different AML subtypes have different prognostic values [22]. FAB subtypes M0, M5, M6, and M7 are associated with the worst prognosis, while M2 and M4 a good prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, this age was lower than that reported in many other studies, which prove the youthful character of the Moroccan AML patients [7-12-23-32-34]. On the other hand study by Sultan et al in the Pakistan population, reported a median age of 37.5 [35] Table 3.…”
Section: Discussionmentioning
confidence: 67%
“…In the study of Padilha et al, patients were predominantly younger than 60 years old (81.6%). Similarly, in the study by Sultan et al 76% of all AML patients ( aged between 15-85) were under 50 years old [35][36]. However, according to SEER statistics patients older than age 65 represent approximately 55% of AML cases [37].This disagreement between studies might be explained by the sample size, the recruitment of pediatric patients, differences in demographic characteristics across countries (the pace of population aging, increased life expectancy…..), environmental and genetic factors which could play a crucial role in the appearance of this cancer at a younger age in our AML patients [38][39].The distribution of the population according to sex revealed a slight male predominance; a similar result was reported in most In AML, leukocytosis is a major prognostic factor.In our series, 13.3% of patients had WBC counts higher than 100.000/mm 3 .…”
Section: Discussionmentioning
confidence: 74%
“…Similar observations have been reported by previously published studies, from Pakistan also revealed comparable age at presentation; 38 and 39 years, respectively. [ 20 21 ]…”
Section: Discussionmentioning
confidence: 99%